The relationship between perceived teacher support and student engagement in Chinese senior high school English classrooms: the mediating role of learning motivation - Zhang, Wenxing; Hu, Jiayue (Frontiers in Psychology, 2025)
IntroductionIn the current educational context, student engagement serves as a key indicator of both teaching quality and overall educational effectiveness in senior high school education.MethodsThis study employed structural equation modeling to analyze the self-report questionnaire data from 314 Chinese senior high school students, aiming to examine the relationship between perceived teacher support and student engagement in English classrooms as well as the mediating role of learning motivation (intrinsic motivation and extrinsic motivation).ResultsThe results indicate that perceived teacher support, learning motivation, and student engagement in English learning are generally moderate to high. There is a positive correlation between teacher support, learning motivation, and student engagement. Teacher support significantly predicts student engagement yet learning motivation plays a mediating role in this relationship, with intrinsic motivation having a greater mediating effect than extrinsic motivation.DiscussionThese findings provide valuable insights into how teacher support influences student motivation and engagement, offering practical strategies for improving instructional approaches in senior high school English education.